2000
DOI: 10.2188/jea.10.74
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Breast Milk Feeding and Atopic Dermatitis in Children

Abstract: Breast milk elevates the risk of atopic dermatitis slightly without statistical significance; the risk may be, however, higher in children in second or later parity orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The 42 records for eczema comprised 24 records from cohort studies , 17 from cross‐sectional studies and one case–control . There were 26 studies from high‐income countries and 14 from middle‐/low‐income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The 42 records for eczema comprised 24 records from cohort studies , 17 from cross‐sectional studies and one case–control . There were 26 studies from high‐income countries and 14 from middle‐/low‐income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 109 publications reached an NOS score indicating high quality, whereas the rest obtained an NOS score of at least 5. 24,31,34,35,39,40,44,[66][67][68][69][70][71][72][73]144,152 Quantitative analysis A meta-analysis of 66 studies (38,505 patients with AD and 203,146 reference individuals) showed that those with a parental history of atopic disease had significantly increased odds of AD (OR, 1.81; 95% CI, 1.65-1.99) (Table I). No significant changes were observed when only high-quality studies were included, or when studies were stratified by geographic area or study size (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…43,184 Limited data examined how other atopic-related diseases such as urticaria, conjunctivitis, and food allergy in parents influenced the risk of AD in offspring. 41,55,70,99 Three birth cohorts investigated the association between maternal symptoms of atopic disease during pregnancy and AD in offspring. A German study found a positive association with symptoms of any atopic disease (adjusted OR, 1.74; 95% CI, 1.00-3.02; P 5 .045), 150 a Canadian study with symptoms of asthma, 171 while an American study found this only for symptoms of AD (RR, 1.70; 95% CI, 1.10-2.60; P 5 .033) and asthma (RR, 1.80; 95% CI, 1.20-2.70; P 5 .015), but not allergic rhinitis (RR, 1.27; 95% CI, 0.91-1.80; P 5 .155).…”
Section: Qualitative Analysismentioning
confidence: 99%
“…The exclusion of non‐English literature may result in language bias. Of the 10 non‐English publications excluded, four were original studies, 59–62 and all suggested no protective effects of breastfeeding on AD. If these four articles were included into the meta‐analysis, the overall effect estimate would be further attenuated toward the null, which would not alter our conclusions.…”
Section: Discussionmentioning
confidence: 99%